Mechanics of Manipulation: A Comparative Analysis of Orwell’s 1984 and Chomsky’s Propaganda Model - Rahman, Afifa (Journal of Research and Multidisciplinary, 2025)
1984 by George Orwell is a remarkable book which can be used to explain the symbiotic relationship between mass media and institutional structures. By using the propaganda model introduced and popularized by Edward S. Herman and Naom Chomskey, this paper intends to assess the components which are used to prompt a certain group of people to fall under a despotic influence where citizens, willingly, yet unwittingly, submit their agency to mass domination. In the process, this paper will investigate the agency of mass media in producing such willing but unwitting submissive citizens much like how "Big Brother" manipulated the citizens of "Oceania" into embracing the cult-like government system. This qualitative research applied the close reading method to thoroughly analyze the interdisciplinary point of view of both media discourse and the totalitarian mindset of powerful institutional structures, like the Party. In their book Manufacturing Consent: The Political Economy of the Mass Media, Herman and Chomsky identifies five media filters to explain the mechanism on which the media industry operates. In 1984, we see Orwell explaining through Emmanuel Goldstein’s book “The Theory and Practice of Oligarchical Collectivism”, how instruments like posters, telescreens, certain ideologies, fabricated news etc. are used to manipulate the perception of reality of the citizens. This paper made a comparative analysis to measure up which of these filters are applicable to the scenario of 1984. The ambit of this paper will be limited to scrutiny of the mechanism which enables all-powerful authority to come into existence rather than investigation of the impact of all- powerful authority on citizens.